Spectral analysis for evaluation of the optical fiber cable performance using experimental and ANN techniques - J. Abbas, H. (International Journal of Engineering and Technology, 2018)
This work deals with the performance evaluation of the optical fiber cables by calculating the changes in the power spectral density, power spectrum, and phase of the response signals from which the faults can be deducted and identified and accordingly the performance can be evaluated. An experimental program has been conducted by exciting the cable and then measuring the power spectral density, power spec-trum, and phase of the response signal for the faulty and un-faulty cables. The calculated and measured results are fed to the ANN system in order to train the ANN program, then the trained ANN package will be used as a parametric study of deduction and identification of cable faults. The ANN system detects and identities the faults in optical fiber. The experimental results power spectral density, power spectrum, and phase measurements are compared with ANN techniques results. Both results showed a good agreement with maximum error less than (1.26%). Finally, the paper shown with vibration test for cable and evaluate for electrical characterizations can be prediction for crack depth or location parameters.Â
Keywords: Detection; Identification; Fault; Power Spectral Density; Power Spectrum; Phase.